Juvenile hyposomatotropism in a Somali cat presenting with seizures due to intermittent hypoglycaemia - Maya Laura König; Diana Henke; Katja Adamik; Cristina Pérez Vera (Journal of Feline Medicine and Surgery Open Reports, 2018)
Case summary A 3-month-old intact male Somali cat was evaluated for a history of seizures, hypoglycaemia and mental dullness 4 weeks after being bitten in the head by a dog. The cat’s body size and weight were approximately half that of his littermates and its haircoat was woolly, with fewer guard hairs. Multiple hypoglycaemic episodes were documented over a period of 4 weeks, which resolved rapidly after correction of the hypoglycaemia. Juvenile hyposomatotropism was presumptively diagnosed by demonstrating low circulating levels of insulin-like growth factor 1 and after exclusion of other endocrine and non-endocrine causes of small stature and hypoglycaemia. The cat’s intermittent hypoglycaemia resolved spontaneously within 1 month and the cat never showed any more neurological signs. Nevertheless, the physical retardation and the coat abnormalities remained unchanged. A year later, the cat was diagnosed with chronic kidney disease IRIS stage 2. Relevance and novel information Hyposomatotropism is an extremely rare feline endocrinopathy. This is the second case reported in the veterinary literature, and the only one to describe hypoglycaemic events associated with growth hormone deficiency. Although hypoglycaemia is one of the most common disease manifestations in children with pituitary dwarfism, this has not yet been reported in veterinary medicine.